IDENTIFIKASI DIAGNOSE KEPERAWATAN DENGAN PENDEKATAN (THE SIX STEPS OF DIAGNOSTIC REASONING METHOD) NOC DAN NIC DI AREA KEPERAWATAN MATERNITAS - Suarni, Lisa (Jurnal Kesehatan Metro Sai Wawai, 2016)
Various problem arised in the Implementation of Function and task of nurses in maternity nursing. For example nurses understanding to nursing process to give standardized nursing care, so it can be  measured.  The aim of this study is to identify nursing diagnosis and to identify NOC and NIC in maternity setting. This is survey analitic with descriptif design. This research consists of two stage. The firs stage is conducted to identify nursing diagnoses of six most frequent cases in maternity setting. The process of identify nursing diagnosis is conducted by researcher.  The second stage is conducted by researcher to identify whether the NOC and NIC chosen based on nursing diagnosis in the first stage are applicable or not in maternity setting.   considered NIC is considered choice in maternity setting if it has total score >8 based on three variables with 1-4 likert scale. The Result is with The 6 steps of diagnostic reasoning method at Nursing diagnoses identify on those six cases are: 13 nursing diagnoses of sectiocaesarea, 9 nursing diagnosis on normal delivery, 7 nursing diagnosis on antepartum hemorraghi, 2 nursing diagnosis on postpartum hemorraghi, 7 nursing diagnosis on preeclampsia/eclampsia, 4 nursing diagnosis on Premature Rupture Membran. Be base on nursing diagnoses/potensial complication are identificationed 43 label NOC and  56 label NIC. Conclusion. The most frequent of cases found is Caesarean sections with most nursing diagnoses identified. It is Be base on identification  label NOC and  NIC  in matternity setting.